2006
DOI: 10.2166/nh.2006.020
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of Icelandic discharge, precipitation and temperature series

Abstract: This study is a part of a Nordic co-operative research project, Climate and Energy, funded by Nordic Energy Research and the Nordic energy sector. The project has the objective of a comprehensive assessment of the impact of climate change on Nordic renewable energy resources including hydropower, wind power, biofuels and solar energy. In this paper, the long term variability of precipitation, temperature and discharge of Icelandic rivers is analyzed with respect to trends. Trend is tested for two periods: 1941… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Trends of hydrologic variables have been investigated by many researchers using different methodologies (Biswas, 2003;Kahya and Kalayci, 2004;Jonsdottir et al, 2006Jonsdottir et al, , 2008Feidas et al, 2007;Kim and Jain, 2010;Yin et al, 2010;Kliment et al, 2011;Tabari et al, 2011;Jhajharia et al, 2012;Ceribasi et al, 2013;Gebremicael et al, 2013;Trajkovic, 2013, 2014;Liu and Zhang, 2013;Kazmierczak et al, 2014). Kahya and Kalayci (2004) investigated the trends of monthly streamflows of Turkey by using Mann-Kendall, Sen's T, the Spearman's Rho and Seasonal Kendall methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trends of hydrologic variables have been investigated by many researchers using different methodologies (Biswas, 2003;Kahya and Kalayci, 2004;Jonsdottir et al, 2006Jonsdottir et al, , 2008Feidas et al, 2007;Kim and Jain, 2010;Yin et al, 2010;Kliment et al, 2011;Tabari et al, 2011;Jhajharia et al, 2012;Ceribasi et al, 2013;Gebremicael et al, 2013;Trajkovic, 2013, 2014;Liu and Zhang, 2013;Kazmierczak et al, 2014). Kahya and Kalayci (2004) investigated the trends of monthly streamflows of Turkey by using Mann-Kendall, Sen's T, the Spearman's Rho and Seasonal Kendall methods.…”
Section: Introductionmentioning
confidence: 99%
“…Kahya and Kalayci (2004) investigated the trends of monthly streamflows of Turkey by using Mann-Kendall, Sen's T, the Spearman's Rho and Seasonal Kendall methods. Jonsdottir et al (2006) investigated the long term variability of precipitation, temperature and discharge of Icelandic rivers using MK test. Feidas et al (2007) examined the trends of annual and seasonal precipitation time series of Greece using MK test and they indicated that annual precipitation generally presents a clear significant decreasing trend for the period 1955-2001, which was determined by the respective decreasing trend in winter precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Alexandersson (1986) developed a standard normal homogeneity test (SNHT) for studying inhomogeneities in the form of abrupt shifts in the mean value of the observations, and Alexandersson and Moberg (1997) later modified the original SNHT for studying inhomogeneities in the form of linear time trends in the mean value of the observations. Since then, this test has been used in a number of studies either for climate data homogenization or for studying climate data discontinuities both in the form of trends and jumps as in Hanssen-Bauer and Førland (1994), Slonosky et al (1999), Tomozeiu et al (2000), Jaagus and Ahas (2000), Tuomenvirta et al (2000), Ducré-Robitaille et al (2003), Klingbjer and Moberg (2003), Jónsdóttir et al (2005), Morales et al (2005), Haimberger (2005), Vicente-Serrano (2006) and Beaulieu et al (2006b). Alexandersson and Moberg (1997) derived critical values of the distribution of the SNHT statistic from relatively short Monte Carlo simulations (MCS) (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This nonparametric method was used to detect the rainfall trend in Australia (Chowdhury, Beecham 2010. Jonsdottir et al (2006) applied the Mann-Kendall method to detect long-term variability of rainfall, temperature and discharge of Iceland Rivers. Annual and seasonal rainfall trends of time series data were investigated by using Mann-Kendall method and showed a significant decreasing trend for the time series in Greece (Feidas et al 2007).…”
Section: Runoff Trend and Potentiality In Melaka Tengah Catchment Of mentioning
confidence: 99%